Porous Nickel Based Half-Cell Solid Oxide Fuel Cell and Thin-Film Yttria-Stabilized Zirconia Electrolyte - A. G. Umirzakov; A. L. Mereke; A. A. Shaikenova; B. A. Rakhmetov; M. A. Yeleuov; R. E. Beisenov; R. Ebrahim; B. A. Mansurov (Eurasian Chemico-Technological Journal, 2021)
In this work, a porous nickel anode for thin-film solid oxide fuel cell prepared by the simple powder hot-pressing method is investigated. Powders of Ni and pore-forming agent (PFA) were thoroughly mixed in different ratios, pressed in a mold and further sintered. The polishing technique with Yttria-Stabilized Zirconia (YSZ) powder has been developed to decrease the surface roughness of Ni-based anode in order to deposit a crack-free electrolyte layer. The 3 μm YSZ thin-film electrolyte was deposited by the pulsed laser deposition technique on the surface of the anode. Morphological and elemental analyses of the samples were characterized by scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) analyses. X-ray diffraction was used for phase analysis and structural characterization. The specific surface areas of the resulting anodes were calculated from their isotherms of N2 adsorption and desorption using the Sorbtometer and calculated by Brunauer Emmett-Teller (BET) method. As a result, the highest mechanical strength and specific surface area (15.42 m2g-1) possessed a sample with the content of PFA equal to 40%, while its ionic conductivity at 800 °C reached 6. 4∙10-2 S/cm.